2010
DOI: 10.1016/j.cub.2010.09.032
|View full text |Cite
|
Sign up to set email alerts
|

Par3 Controls Epithelial Spindle Orientation by aPKC-Mediated Phosphorylation of Apical Pins

Abstract: Summary Background Formation of epithelial sheets requires that cell division occurs in the plane of the sheet. During mitosis, spindle poles align so the astral microtubules contact the lateral cortex. Confinement of the mammalian Pins protein to the lateral cortex is essential for this process. Defects in signaling through Cdc42 and atypical protein kinase C (aPKC) also cause spindle misorientation. When epithelial cysts are grown in 3D cultures, mis-orientation creates multiple lumens. Results We now sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

24
261
4

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 220 publications
(291 citation statements)
references
References 31 publications
(57 reference statements)
24
261
4
Order By: Relevance
“…Previous studies have indicated that polarization in stem cells is necessary for asymmetrical divisions 14,15 . However, other studies reported that polarization that is associated with tight junctions or adherens junctions promotes symmetrical divisions [27][28][29] . To determine the polarization patterns of the prostate epithelium, we performed double immunofluorescence of prostate sections with p63, CK8 and antibodies against the polarization molecules Par3 and aPKC.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Previous studies have indicated that polarization in stem cells is necessary for asymmetrical divisions 14,15 . However, other studies reported that polarization that is associated with tight junctions or adherens junctions promotes symmetrical divisions [27][28][29] . To determine the polarization patterns of the prostate epithelium, we performed double immunofluorescence of prostate sections with p63, CK8 and antibodies against the polarization molecules Par3 and aPKC.…”
Section: Resultsmentioning
confidence: 98%
“…Cell polarity is one important feature of the epithelium 49 and has been shown to affect cell division modes 14,27 and tumorigenesis 50,51 . Our study indicates that the different expression patterns of the Par3 protein are observed in luminal and basal cells (Supplementary Fig.…”
Section: Discussionmentioning
confidence: 99%
“…5d,e). Staining with the tight junction marker ZO-1 revealed that apicobasal polarity is not affected in FAK morphants, whereas other polarized molecules involved in spindle orientation like the Par6/3-aPKC complex also remain properly localized even in cells with completely misoriented spindles 45,46 ( Supplementary Fig. 6a-c).…”
Section: Z=1 Z=3mentioning
confidence: 99%
“…For example, erratic alignment of the mitotic spindle could enable efficient expansion of a cell mass in every direction, thus promoting hyperplasia. Out-of-alignment mitotic spindle may also increase aneuploidy [5,23]. Altered cell adhesion and extracellular matrix-dependent signalling mechanisms may make cells more migratory [24], loss of lipid asymmetry may deregulate spatial PI3K signalling and any cell-intrinsic (e.g.…”
Section: Loss Of Epithelial Polarity In Cancermentioning
confidence: 99%
“…The molecular asymmetries guide directional exocytosis and secretion of digestive enzymes from pancreas, milk from mammary epithelium and vectorial transfer of nutrients across the gut epithelium to blood [1]. Furthermore, extension of epithelial monolayers requires that cell divisions occur in the plane of the sheet and many key cell polarity proteins are involved in determining alignment of the mitotic spindle so that it is perpendicular to the axis of apico-basal polarity [4][5][6]. In addition to many proteins, lipids are also asymmetrically distributed in polarized cells [1].…”
Section: Loss Of Epithelial Polarity In Cancermentioning
confidence: 99%